The Effect of the Implementation of Green Accounting and Corporate Social Responsibility (CSR) on Company Profitability (Case Study on Textile and Garment Industry Companies Listed on the IDX) - Esra Gea, Esra Graciela Valerina Gea; Tri Wulandari (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to analyze the effect of the application of green accounting and corporate social responsibility (CSR) on company peroactivity in the case study of textile and garment industry companies on the IDX. This study uses quantitative data with secondary data sources. The population of this study is 22 companies listed on the IDX for the 2020-2023 period, sampling by purposive sampling so that the number of samples used is 15 companies and observations are carried out as many as 60 observations. The data analysis techniques used were multiple linear regression, classical assumption test and hypothesis test. The results of the study show that green accounting and CSR partially and simultaneously have a positive and significant effect on the profitability of textile and garment companies listed on the IDX. There is a strong correlation between green accounting and CSR and company profitability and the percentage of 32.8% and the remaining 67.2% can be accounted for by other variables outside the scope of the study that were not conducted.